PERUBAHAN SEBARAN LIMBAH AIR PANAS PT. PJB UP MUARA KARANG AKIBAT MASTERPLAN REKLAMASI - Alfath Islami; Rudhy Akhwady; M Mauludiyah (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2020)
ABSTRACTThe reclamation master plan in muara karang waters has the potential to influence the hydrodynamic conditions and the temperature distribution of the waters affected by the inclusion of hot water waste from the PT.PJB UP muara karang power plant activities. The purpose of this study is to determine changes in current patterns and the heat distribution of waste water from PT. PJB UP muara karang due to the reclamation master plan in muara karang waters, north Jakarta. this research uses hydrodynamic modeling. The hydrodynamic modelling is based on continuity and momentum equations. The model produced in this study is quite in accordance with field conditions with a relative error value less than 15%. the conditions of reclamation masterplan result the change of current patterns, especially around the intake canal where the current velocity decreased due to obstruction of water mass flow by islands g and h and the canal boundary on both. the changes of the current pattern inflicted the changes of distribution pattern of heat water waste in muara karang. Increased water temperatures due to the reclamation masterplan occur in the western and eastern areas with a difference in water temperature of 0.35oc - 1oc compared to post reclamation conditions. this is inversely proportional to the temperature in the area around the intake canal which is decreased with a temperature difference of -1oc to -3oc.keyword: Reclamation, Thermal dispersion, ModelingABSTRAKRencana induk reklamasi di perairan Muara Karang berpotensi mempengaruhi kondisi hidrodinamika dan distribusi temperatur perairan yang dipengaruhi oleh masuknya limbah air panas dari kegiatan PLTU PT.PJB UP Muara Karang. Tujuan dari penelitian ini adalah untuk mengetahui perubahan pola arus dan distribusi kalor air limbah dari PT. PJB UP Muara Karang karena adanya rencana induk reklamasi di Perairan Muara Karang, Jakarta Utara. Penelitian ini menggunakan pemodelan hidrodinamik. Pemodelan hidrodinamika didasarkan pada persamaan kontinuitas dan momentum. Model yang dihasilkan pada penelitian ini cukup sesuai dengan kondisi lapangan dengan nilai error relatif kurang dari 15%. Kondisi masterplan reklamasi mengakibatkan terjadinya perubahan pola arus terutama disekitar intake canal dimana kecepatan arus menurun akibat terhambatnya aliran massa air oleh pulau G dan H serta batas saluran pada keduanya. Perubahan pola arus tersebut menyebabkan terjadinya perubahan pola sebaran limbah air panas di Muara Karang. Peningkatan suhu air akibat masterplan reklamasi terjadi di wilayah barat dan timur dengan perbedaan suhu air 0,35oC - 1oC dibandingkan kondisi pasca reklamasi. Hal ini berbanding terbalik dengan temperatur di sekitar saluran intake yang mengalami penurunan dengan perbedaan temperatur -1oC sampai -3oC.Kata Kunci: Reklamasi; Sebaran Panas; Pemodelan